Understanding the Contextual Factors Affecting Women's Health in Sistan and Baluchestan Province in Iran A Qualitative Study - Rezaee, Nasrin PhD (International journal of community based nursing and midwifery, 2017)
BACKGROUND: Contextual factors impact health the same way social and cultural conditions do. Women's health, with its varying dimensions, is also under the influence of biological, societal, and cultural contexts. This typical condition has been developed along the continuum of their life cycle, bearing close correlation with their lif style. Therefore, identifying those marices within which women's health behaviors are formed is important.This study aims at exploring the contextual factors affecting women's health in Sistan and Baluchestan in Iran